Visible light-induced enhancement in the Seebeck coefficient of PEDOT:PSS composites with two-dimensional potassium poly-(heptazine imide). Issue 2 (17th December 2021) - Li, Binrong; Yue, Shizhong; Cheng, Hanlin; Wu, Chundu; Ouyang, Jianyong
Abstract : The Seebeck coefficient of the composites of PEDOT:PSS and two-dimensional poly-(heptazine imide) (KPHI) can be greatly enhanced after exposure to visible light. It is attributed to the light-induced electron transfer from KPHI to PEDOT:PSS. Abstract : Thermoelectric (TE) materials are significant for sustainable development because they can be used to directly harvest heat and convert it into electricity. Although it is well known that light exposure can affect the electrical properties of semiconductors, there is no report on the enhancement of the Seebeck coefficient of materials through exposure to visible light. Here, we report the visible light-induced enhancement in the Seebeck coefficient of the composites of poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) dispersed with two-dimensional potassium poly-(heptazine imide) (KPHI) that can absorb visible light. Exposure of a KPHI/PEDOT:PSS composite with a KPHI loading of 53.6 wt% to visible light can enhance the Seebeck coefficient from 25.9 to 69.2 μV K −1 . The light exposure can also enhance the power factor of a double-layer composite with a KPHI layer and a PEDOT:PSS layer from 147.2 to 227.9 μW m −1 K −2 . The enhancement in the Seebeck coefficient is attributed to the visible light-induced electron excitation from the valence band to the conduction band of KPHI and subsequent electron transfer to PEDOT:PSS, leading to the dedoping and Seebeck coefficient enhancement.